Three operational models for ambidexterity in large corporations - Sverker Alänge; Annika Steiber (Triple Helix, 2018)
This paper examines new approaches that large firms are using to become more ambidextrous-more able to "explore" and innovate for the future while they "exploit" current lines of business. It presents and compares three different models for boosting innovation by partnering with external actors: GE Appliances' FirstBuild unit for new-product development, the Open Innovation function at Electrolux, and Lantmännen's Greenhouse corporate accelerator program. The models are early-stage but have started generating product and business-model innovations, planting seeds of cultural change in the parent firms, and building external ecosystems with partners that range from startup companies to individual developers and makers.
Keywords: 330; Ambidexterity; Dynamic capabilities; Operational models